Pendidikan Lingkungan dan Pembangunan Berkelanjutan dalam Pendidikan Agama Islam - Reni Susilawati; Zjulpi Andriansah; Shalicha Nafilata Erhassa; Nanda Inka Fitri; Wan Jamaluddin (Program Pascasarjana IIQ Jakarta, 2024)
Problems related to the environment are becoming global issues that are increasingly urgent to be addressed. Various problems related to climate change, environmental degradation and the reduction of natural resources have brought serious threats to human survival and the ecosystems that support them. Uncontrolled human activities such as overexploitation of resources, deforestation, and air, land and water pollution have had widespread and detrimental impacts. This situation demands a change in the development paradigm that is not only oriented towards economic growth, but also towards a balance between human needs and environmental sustainability. In an effort to realize sustainable development, environmental education has a strategic role that cannot be ignored. Environmental education provides society, especially the younger generation, with the knowledge, attitudes and skills needed to live in harmony with the environment. This educational process not only aims to increase understanding of the importance of protecting the environment, but also builds awareness of the long-term impacts of every action taken. In this way, environmental education can create future generations who are more responsible in maintaining the balance of the ecosystem. Therefore, it is very important to study issues related to Environmental Education and Sustainable Development in Islamic Religious Education. By using descriptive analysis methods through literature studies or library research, the author tries to examine every aspect of Environmental Education and Sustainable Development in Islamic Religious Education so that it can produce insight, knowledge, and as a view to develop a guideline, reference in carrying out the educational process.